A religiosidade popular na Revista Família Cristã: uma análise das matérias que aparecem na seção Cultura Popular das edições de 1980 a 1981 - Nascimento, Maria Natividade Pereira do (2007)
Família Cristã magazine has started in Italy as an important vehicle to accomplish the dream of Saint Paul´s Society´s Founder who wanted to spread the Gospel all over the world by using modern media. The magazine was founded in Brazil in 1934. In its beginning it was only a leaflet, but to-day it is one of the most spread magazines that propagate religion and Catholicism in Brazil. In the magazine, we outlined the object of our research, by focusing the matters of the Section Cultura Popular (Popular Culture) in the years 1980 and 1981. After an introduction about Saint Paul´s Society, its Founder and about the origin and evolution of the magazine in Italy and in Brazil, we described the Section and commented the topics that disclose the catholic popular culture and religion. Then we organized the subjects in five themes: devotions, folklore and folkloric rhythms, myths of popular faith, pilgrimages, and saints. Based on theoretical references, we analyzed the aspects of the popular religiosity that appear in the matters. The magazine´s purpose is to describe and to expose the subjects without special intention of analyzing and commenting them. However, in our research, we found a richness of themes for religious studies. The religious atmosphere of the matters may be red in the light of Puebla´s Conference description of catholic popular religiosity. The subjects we studied gave chance to point out a rich repertory of cultural, religious and existential values of the popular religiosity that indicate concretely and deeply the encounter of the divine and the human life, that goes further than the ritual manifestations and creates a peculiar vision of the world, the so called sensus fidei that makes the sacred always present in all aspects of life